KERJASAMA BNP2TKI DENGAN IOM DALAM MENANGANI HUMAN TRAFFICKING TENAGA KERJA INDONESIA DI MALAYSIA PERIODE 2011-2015 - Ayu Wulandari, Ajeng Ria; Windiani, Reni; Putranti, Ika Riswanti (Journal of International Relations, 2016)
Malaysia is one of major destination countries for Indonesian migrant workers. Thisfact has been triggering many transnational crimes, including human trafficking,Despite Indonesian government has been reduced the number of migrant workerssignificantly from 2011 to 2015, the problem of human trafficking remains occur. Inorder to combat human trafficking from Indonesia to Malaysia Indonesiangovernment through the National Agency for The Placement and Protection ofIndonesian Workers (BNP2TKI)in cooperation with International Organization forMigration (IOM), made an effort to prevent human trafficking. This research aimedto describe the implementation of the cooperation between two agencies in handlingthis issue. This research employed qualitative approach through library research aswell as deep interviews. This research found that two agencies had been succeded toimplement the cooperation that had settled before. Two agencies employ variousstrategies such as campaign and socialization to migrant workers prospectus,training and capacity building, publishing guide book concerning legal workingabroad.